A Case Control Study on Risk Factors Associated with Malnutrition in Dolpa District of Nepal - Mehata, Suresh (Journal of Food Science and Technology Nepal, 2009)
Malnutrition remains a serious obstacle to child survival, growth and development in Nepal. The most common forms are protein-energy malnutrition (PEM) and micronutrient deficiency states (iodine, iron and vitamin A deficiency). A case-control study design was used. Case were defined as malnutrition (Weight-for- Age Z- score <- 1.96 SD). Controls were defined as neighborhood population of same age group selected randomly from the same VDC. A total of 105 cases 112 controls were selected. All parents of cases and controls were interviewed face-to-face using a semi-structure questionnaire after anthropometric measurement of children. In addition to general background information, respondents were asked questions about suspected risk factors.Among the risk factors; immunization, age, educational status of mother, Iron tablet during pregnancy and antenatal checkup shows a significant risk association with malnutrition. Immunization (OR = 2.18), age of children (OR = 1.023) and education of mother (OR = 2.134) as well as positive risk association between malnutrition and iron supplementation during pregnancy (OR=1.993) and ANC (OR = 2.167). However, vitamin A supplementation, de-worming tablets, number of family members in the family and working hours of mother does not reach statistical significance. Socio-demographic factors: low maternal education, immunization and poor feeding practices for children are affecting children's health regarding malnutrition. Key words: Malnutrition; Z-score; Education of mother; Antenatal check-up (ANC) Journal of Food Science and Technology Nepal Vol. 4, September, 2008, Page: 34-37